THE DEVELOPMENT OF HIERARCHY EFFECTS AIDA (ATTENTION, INTEREST, DESIRE, ACTION) MODEL IN COMMUNICATION BRANDING STRATEGY OF TEPAL-SUMBAWA COFFEE - Ayu Ardhanariswari, Kartika; Krisnandini Wahtu Pratiwi; Ninik Probosari; Ari Wijayani (Dinasti Publisher, 2020)
Indonesia as one of the largest coffee-producing countries in the world, which ultimately has an impact on the coffee industry and the trend of consuming coffee. Tepal Coffee as a typical product of Sumbawa, West Nusa Tenggara has uniqueness and superiority when compared to coffee in other regions. A National Coffee Board study revealed that it is very rare that Arabica coffee has low acidity and is only found in Tepal Coffee in Sumbawa Regency. The uniqueness is one of the advantages of Tepal Coffee which must be raised, branding, and popularized so that the market demand for Sumbawa typical coffee will have an impact on improving the welfare of Sumbawa farmers. The purpose of this research is to find out the AIDA Hierarchy of Effects Model in developing the branding communication strategy in Tepal Coffee. The method used in this study uses qualitative descriptive methods. The result has been shown that the Implementation of Brand Communication Strategy of Tepal-Sumbawa Coffee in building awareness has been done by using Brand visualization with Packaging and brand activation with advertising, events, direct marketing, and Social Media. The level of brand awareness of Tepal Coffee Sumbawa is at the level of Brand Recognition. In this research, the position of Tepal Coffee branding approach is needed to find a broad market, through product branding is important for the long-term achievement of coffee as an economic commodity.